Pinch combined with exergy analysis for heat exchange network and techno-economic evaluation of coal chemical looping combustion power plant with CO2 capture. (1st January 2022) - Zhao, Ying-jie; Zhang, Yu-ke; Cui, Yang; Duan, Yuan-yuan; Huang, Yi; Wei, Guo-qiang; Mohamed, Usama; Shi, Li-juan; Yi, Qun; Nimmo, William
Abstract: A coal chemical looping combustion (CLC) power plant (600 MW) with CO2 capture was established and validated. The key operation parameters and conditions for the coal chemical looping combustion process were tested and optimized. Heat exchange network (HEN) was established and optimized using the combined pinch and exergy analysis method for matching and integrating different levels or grade energy, from flue gas and exhaust steam waste heat, in coal chemical looping combustion power plant to maximize the energy efficiency output. Followed by conducting a techno-economic evaluation and exergy distribution analysis which showed that the net energy efficiency of the CLC power plant (34.8 %, improved by 1.9 %) is 2.4 % higher than the monoethanolamine (MEA)-based ultra-supercritical coal power plant (32.4 %) with the same CO2 capture ratio (90 %). The CLC power plant also provides a lower cost of electricity (0.088–0.127 $/kWh) and less coal consumption (381 g/kWh), compared to the MEA-based power plant (0.143 $/kWh, 408 g/kWh). The cost and energy penalty of CO2 enrichment and separation are less when compared to traditional MEA-based ultra-supercritical coal power plants due to the intrinsic nature of in-suit CO2 capture, the lower exergy destruction in the chemical looping combustion process, and sufficient energy integration and recovery from HEN. Graphical abstract: Image 1 Highlights: HEN of CLC power plant with CCS is optimized using CPEA method. Net exergy efficiency of CLC power plant improves by 1.9 %. Coal consumption and CO2 emission of CLC power plant reduce by 6.9 % and 7.2 %. COE of CLC (0.088–0.127 $/kWh) is lower than COE of MEA-power plant (0.143 $/kWh).